Molecular characterization and diversity analysis of bacterial communities associated with Dialeurolonga malleswaramensis (Hemiptera: Aleyrodidae) adults using 16S rDNA amplicon pyrosequencing and FISH. (19th May 2015) - Pandey, Neeti; Rajagopal, Raman
Abstract: Dialeurolonga malleswaramensis Sundararaj (Hemiptera: Aleyrodidae) is a phytophagous sap sucking insect. It infests Polyalthia longifolia, an important avenue tree of India, effective in alleviating noise pollution and having immense medicinal importance. Samples of this insect were collected from Polyalthia longifolia . The cytochrome c oxidase subunit I gene ( mtCO1 ) helped in the molecular characterization of the insect. This study reports the bacterial diversity in D. malleswaramensis adults by high throughput 16S rDNA amplicon pyrosequencing. The major genera identified were Portiera and Arsenophonus . Other bacterial genera detected were uncultured alpha proteobacterium, Sphingopyxis and Methylobacterium . We also employed fluorescence in situ hybridization (FISH) in whole mount samples to confirm the presence of dominant endosymbionts Portiera and Arsenophonus to the bacteriocyte of D. malleswaramensis . This study concludes that combining techniques like 16S rDNA amplicon pyrosequencing and FISH reveal both dominant and rare bacteria. The data also predict the evolutionary position of this pest with respect to other whitefly species using a mitochondrial marker.